Punjab Debt Sustainability Analysis - Manoel, Alvaro; Refaqat, Saadia; Onder, Harun; Ashraf, Mehwish (World Bank, Washington, DC, 2014)
Punjab is Pakistan's most populous and economically vibrant province. Its fiscal health, therefore, is crucial to the fiscal stability and economic development of Pakistan as a whole. By end-June 2011, Punjab's outstanding debt stood at Rs. 413 billion, or 4.0 percent of Gross Subnational Domestic Product (GSDP). The low debt level is perhaps not surprising given the historical barriers to borrowing imposed at the federal level. But this has changed profoundly with enactment of the 18th Constitutional Amendment which has allowed provinces to borrow domestically and externally, subject to limits imposed by National Economic Council (NEC). This change has heightened the need to examine what Punjab owes and the question of provincial debt sustainability in general. As there is no threshold defined for subnational debt levels, this sustainability analysis considers unsustainable fiscal policies and borrowing strategy to be those that lead to an explosive accumulation of debt such that it would jeopardize the normal provision of services by the province. The analysis projects the debt outlook through the fiscal years 2012 to 2021, using the Government of Punjab's current Medium-Term Fiscal Framework (MTFF) as the base. The MTFF for fiscal 2012 anticipates fiscal surpluses in medium term, driven mainly by an improvement in provincial finances due to a favorable Seventh National Finance Commission Award, and thus concludes that the debt outlook is sustainable through fiscal 2021: the debt-to-GSDP ratio gradually declines over the next 10 years, to 1.2 percent, from 4.0 percent; the interest payments-to-revenues ratio decreases to 0.9 percent, from 3.0 percent; while the debt service-to-revenues ratio rises by a modest 0.3 percent to 3.3 percent. The analysis then explores some potential vulnerability to economic and fiscal shocks. Punjab's debt sustainability to be fairly robust to most shocks, except when the individual shocks are combined. However, the probability of combined shock remains very low.